Game Edukasi Matematika berbasis Android - Septi Fajarwati; Riswati Riswati; Tri Astuti (IKIP PGRI Bojonegoro, 2021)
Abstract: The process of teaching and learning activities implemented at SD Negeri 3 Tanjunganom still uses conventional methods. Even though the school has provided android facilities for students to support learning, this has not been utilized properly by teachers including mathematics teachers, so that many students have difficulty understanding mathematics, especially in the sub-material of building cubes and blocks. This is evidenced by the low average value obtained when compared to other subject matter. The purpose of this research is to create learning media for mathematics education games to build android-based cubes and blocks. So it is hoped that it can help teachers in learning in class and is also expected to make it easier for students to understand the material, especially the sub-material of building cubes and blocks. Applications that are made are developed using the Multimedia Development Life Cycle (MDLC) method, namely drafting, designing, collecting materials, manufacturing, testing, and distribution. The result of this research is that mathematics education game has been successfully created with android based sub-material building blocks and cubes. The results of the Beta test, which involved 30 respondents, obtained an average of 88% strongly agree, meaning that the application of math education games to build cubes and blocks is made attractive and easy to use by students of SD Negeri 3 Tanjunganom, especially class V. Keywords: Mathematics, Educational Games, Android Abstrak: Proses kegiatan belajar mengajar yang diterapkan di SD Negeri 3 Tanjunganom masih menggunakan cara konvensional. Meskipun pihak sekolah telah menyediakan fasilitas android untuk siswa guna menunjang pembelajaran, akan tetapi hal tersebut tidak dimanfaatkan dengan baik oleh para guru termasuk guru matematika, sehingga banyak siswa yang mengalami kesulitan dalam memahami pelajaran matematika khususnya pada sub materi bangun ruang kubus dan balok. Hal tersebut dibuktikan dengan nilai rata-rata yang diperoleh masih rendah jika dibandingkan dengan muatan pelajaran lainnya. Tujuan dari penelitian ini adalah untuk membuat media pembelajaran game edukasi matematika bangun ruang kubus dan balok berbasis android. Sehingga diharapkan dapat membantu guru dalam pembelajaran di kelas dan juga dapat memudahkan siswa dalam memahami materi terutama sub materi bangun ruang kubus dan balok. Aplikasi yang dibuat dikembangkan dengan metode Multimedia Development Life Cycle (MDLC) yaitu Pengonsepan, Perancangan, Pengumpulan Bahan, Pembuatan, Pengujian, dan Distribusi. Hasil dari penelitian ini adalah telah berhasil dibuat game edukasi matematika sub materi bangun ruang kubus dan balok berbasis android. Hasil pengujian Beta test yang melibatkan 30 responden diperoleh rata-rata 88% sangat setuju, artinya bahwa aplikasi game edukasi matematika bangun ruang kubus dan balok yang dibuat menarik dan mudah digunakan oleh siswa SD Negeri 3 Tanjunganom khususnya kelas V. Kata kunci: Matematika, Game Edukasi, Android